Analysis of Stress and Fracture Strength of Zirconia Implants after Cyclic Loading - Cruvinel,Diogo Rodrigues (2015)
AbstractThe aim of this study was to manufacture a new zirconia implant (Y-TZP) and to evaluate the fracture strength and stresses generated after cyclic loading compared to titanium implants. Thirty-three zirconia and titanium implants were fabricated. The stress generated around the implants was observed by photoelastic analysis. The implants were then separated into groups (n = 10): Control (no treatment), mechanical fatigue and thermomechanical fatigue. All groups were submitted to a single cantilever flexure test to measure the material fracture strength. The results (2-way ANOVA, Bonferroni test, p <.05) showed no statistically significant difference in the stresses generated between the zirconia and titanium implants. Titanium implants showed higher fracture strength than the zirconia implants, a property that was not altered by fatigue applied. It was concluded that stress distribution was similar for Zr and Ti and mechanical and thermomechanical fatigue had no influence on the fracture strength of the implants tested.